Multiple Fractures of Cervical Vertebrae Combined with Arcuate Foramen and Vertebral Artery Occlusion: A Case Report and Literature Review - Wei‐hao Wang; Zhao‐yong Liu; Huan‐cheng Guo; Hu Wang (Orthopaedic Surgery, 2021)
Background The arcuate foramen is a complete or partial bony bridge over the vertebral artery groove of atlas. The mechanism of the arcuate foramen is not clearly understood. Omission of the arcuate foramen sometimes causes lethal iatrogenic injury during spinal surgery. Case Presentation We describe a patient who was diagnosed with multiple fractures of the cervical vertebrae, arcuate foramen, and right vertebral artery occlusion based on clinical and radiological exams. After conservative treatment, he resumed a normal and productive life. Conclusions Arcuate foramen is a common variation that causes symptoms such as dizziness, headache, and migraine. If the patient does not develop severe symptoms, conservative treatment can achieve very good results without the necessity to remove the bone bridge. When serious symptoms occur, surgical treatment to resect the bony ridges can relieve the symptoms dramatically.